Translated Attributes as Choice Architecture: Aligning Objectives and Choices Through Decision Signposts - Ungemach, Christoph; Camilleri, Adrian R.; Johnson, Eric J.; Larrick, Richard P.; Weber, Elke U. (Management Science, 2018)
Every attribute can be expressed in multiple ways. For example, car fuel economy can be expressed as fuel efficiency (“miles per gallon”), fuel cost in dollars, or tons of greenhouse gases emitted. Each expression, or “translation,” highlights a different aspect of the same attribute. We describe a new mechanism whereby translated attributes can serve as decision “signposts” because they (1) activate otherwise dormant objectives, such as proenvironmental values and goals, and (2) direct the person toward the option that best achieves the activated objective. Across three experiments, we provide evidence for the occurrence of such signpost effects as well as the underlying psychological mechanism. We demonstrate that expressing an attribute such as fuel economy in terms of multiple translations can increase preference for the option that is better aligned with objectives congruent with this attribute (e.g., the more fuel-efficient car for those with proenvironmental attitudes), even when the new information is derivable from other known attributes. We discuss how using translated attributes appropriately can help align a person’s choices with their personal objectives. The online appendix is available at https://doi.org/10.1287/mnsc.2016.2703 . This paper was accepted by Yuval Rottenstreich, judgment and decision making.